1987
DOI: 10.1111/j.1532-950x.1987.tb00940.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Strength and Holding Power of 4 Pin Designs for Use with Half Pin (Type I) External Skeletal Fixation

Abstract: The strength and holding power of four pin designs for use with half pin (type I) external skeletal fixation were evaluated. Pins that were tested were fully threaded, nonthreaded, two cortices partially threaded, and one cortex partially threaded. The study involved three parts: (1) resistance of the pins to axial extraction immediately after insertion; (2) resistance of the pins to axial extraction 8 weeks after being inserted into the tibiae of live dogs; and (3) resistance of the pins to bending load. Pins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 5 publications
2
60
0
Order By: Relevance
“…We evaluated the force required for axial extraction of pins from avian bone immediately after insertion (acute study). Our results, which are consistent with other studies, 13–15,17 showed that smooth pins had relatively little resistance to axial extraction whereas threaded pins had significantly more holding power in all bone locations. For a specific pin type, we did not observe differences in pullout strength between humerus and tibiotarsus in spite of differences in osseous structure and the thicker cortex in the tibiotarsus.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We evaluated the force required for axial extraction of pins from avian bone immediately after insertion (acute study). Our results, which are consistent with other studies, 13–15,17 showed that smooth pins had relatively little resistance to axial extraction whereas threaded pins had significantly more holding power in all bone locations. For a specific pin type, we did not observe differences in pullout strength between humerus and tibiotarsus in spite of differences in osseous structure and the thicker cortex in the tibiotarsus.…”
Section: Discussionsupporting
confidence: 93%
“…Commercial orthopedic pins have been mostly designed for mammals not birds. Previous reports of the influence of pin design on bone holding power in mammals and birds suggest that threaded pins have greater holding power in axial extraction than smooth pins 13,15,17 . Reportedly, thread pitch has little effect on pullout forces of fixation pins and screws 18,19 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, using an increased number of pins per segment in clinical situations dispersed weight-bearing loads that are concentrated at the pin-bone interface over a larger area, thus theoretically decreasing the incidence of pin loosening. 18,26,28 In contrast, the use of additional fixation pins requires penetration of large-muscle masses (eg, involving the proximal humerus, femur, or tibiotarsus). From the clinical experience at The Raptor Center, pin-tract drainage is rarely encountered with adequate postoperative care.…”
Section: Discussionmentioning
confidence: 94%